High-impervious durable mineral blended sludge solidifying agent and preparation method thereof

CN122355651BActive Publication Date: 2026-10-16HUBEI SHANSHUFENG BUILDING MATERIALS TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610827758.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-06-09
Publication Date
2026-10-16
Estimated Expiration
2046-06-09

AI Technical Summary

Technical Problem

[0006]有鉴于此,本发明的目的在于提出一种高抗渗耐久型矿物掺合淤泥固化剂及其制备方法,以解决现有淤泥固化技术中,因改性手段简单叠加或无序掺混,导致固化体内部的微观结构优化不足,无法同步实现高强度、高抗渗与优异干湿循环耐久性的技术问题

Benefits of technology

首先,基于γ-氨丙基三乙氧基硅烷的预水解与接枝处理,显著改善了矿物掺合基粉在后续液相改性中的分散性及表面活性,为后续功能组分的逐级、有序负载提供了稳定且均匀的界面基础,避免了有机硅烷在后期整体拌和时被无效消耗或包裹。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122355651B_ABST
    Figure CN122355651B_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of curing agent, in particular to a high anti-permeability durability type mineral mixed sludge curing agent and a preparation method thereof.The curing agent is composed of modified mineral mixed particles, ordinary Portland cement and calcium oxide.The core is to prepare modified particles through a step-by-step process: first, grafting silane to metakaolin and silica fume, then introducing acidic small particle size and alkaline large particle size silica sol in sequence, and introducing sodium methyl silicate when the material loss on drying is 4%-6%.The design can synergistically optimize the microstructure of the cured body, preferentially densify in the fine pores, and form a delayed hydrophobic barrier on the outer layer, thereby synergistically improving the unconfined compressive strength, impermeability and durability of the cured sludge after dry-wet cycles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of curing agent technology, and in particular to a highly impermeable and durable mineral-blended sludge curing agent and its preparation method. Background Technology

[0002] Silt, a common dredging and engineering waste, presents a serious challenge to resource utilization due to its high water content, high clay content, and complex pollutant distribution. Directly dumping or landfilling silt not only occupies a large amount of land but also poses a risk of secondary environmental pollution. Therefore, solidification and stabilization treatment is an important way to achieve both harmlessness and resource utilization.

[0003] Currently, the common practice for sludge solidification is to use inorganic cementitious materials such as ordinary silicate cement, lime, and slag as the main components. This type of technology primarily utilizes hydration reactions to generate gel products such as hydrated calcium silicate, which encapsulate soil particles and create a certain strength. However, for sludge with high water content and high clay content, the presence of a large amount of free water severely dilutes the concentration of the cementitious materials, and the strong water absorption of clay minerals can delay or even hinder the hydration process. This leads to the formation of interconnected pores and seepage channels within the solidified body, allowing water, dissolved salts, and pollutants to easily migrate. Consequently, the long-term impermeability and durability of the solidified body, especially its volume stability and strength retention under harsh environments such as wet-dry cycles, are difficult to meet engineering requirements.

[0004] To improve impermeability, existing technologies attempt to directly incorporate organosilicon waterproofing agents (such as sodium methylsilicate) or nanomaterials (such as silica sol) into the curing system. Sodium methylsilicate can form a hydrophobic film on the pore surface, providing significant short-term waterproofing. However, in highly alkaline sludge curing systems with multiple minerals, its active ingredients are easily consumed or encapsulated, making it difficult to distribute evenly in key pore throat areas. Furthermore, it may react prematurely, interfering with the main gelation process and hindering strength development. Its hydrophobic effect also tends to diminish under alternating wet and dry stress. Silica sol, especially nano-silica sol, can fill pores and promote hydration, but different types and particle sizes of silica sol exhibit significantly different behaviors in complex systems.

[0005] In summary, existing technologies either simply juxtapose inorganic curing with organic / nano-modification methods or randomly mix different modifying materials. This often results in the improvement of the impermeability of the cured body at the expense of strength, or the impermeability effect obtained is temporary and superficial, and cannot maintain stable performance under durability tests such as wet-dry cycles. In other words, it is difficult to synergistically optimize the three aspects of strength, impermeability, and durability, which has become a key bottleneck restricting the utilization of high-value resources. Summary of the Invention

[0006] In view of this, the purpose of this invention is to propose a high-permeability and durable mineral-blended sludge solidifying agent and its preparation method, so as to solve the technical problem in the existing sludge solidification technology that the microstructure optimization inside the solidified body is insufficient due to the simple superposition or disordered mixing of modification methods, and the inability to simultaneously achieve high strength, high permeability and excellent dry and wet cycle durability.

[0007] To achieve the above objectives, the present invention provides a mineral-blended sludge solidifying agent, comprising, by weight: 365-386 parts of modified mineral blended particles, 450-550 parts of ordinary silicate cement, and 100-140 parts of calcium oxide.

[0008] The modified mineral blend particles are obtained by grafting metakaolin and silica fume with γ-aminopropyltriethoxysilane, followed by the sequential introduction of acidic silica sol with a particle size of 8-15 nm and alkaline silica sol with a particle size of 20-60 nm, and the introduction of sodium methylsilicate aqueous solution when the weight loss rate is 4%-6%; the weight loss rate is the percentage of the mass reduction before and after drying at 105℃ for 30 min relative to the mass before drying.

[0009] The raw materials used to prepare the modified mineral blend particles, by mass, include 220-270 parts metakaolin, 80-130 parts silica fume, 10-14 parts γ-aminopropyltriethoxysilane, 20-28 parts acidic silica sol with a particle size of 8-15 nm, 14-22 parts alkaline silica sol with a particle size of 20-60 nm, and 10-14 parts aqueous solution of sodium methylsilicate.

[0010] Preferably, the γ-aminopropyltriethoxysilane is introduced in the form of a pre-hydrolyzed solution, which is composed of 80-100 parts by mass of anhydrous ethanol, 8-12 parts by mass of deionized water, 0.8-1.2 parts by mass of glacial acetic acid and 10-14 parts by mass of γ-aminopropyltriethoxysilane.

[0011] Preferably, the sodium methylsilicate aqueous solution is premixed with deionized water before introduction.

[0012] Preferably, the modified mineral blend particles are particles obtained by grinding and passing through a 200-mesh sieve.

[0013] Preferably, the grade of the ordinary silicate cement is P·O42.5.

[0014] Furthermore, the present invention also provides a method for preparing a mineral-blended sludge solidifying agent, comprising the following steps: (1) After drying, metakaolin and silica fume are mixed to obtain mineral admixture base powder; (2) γ-aminopropyltriethoxysilane is pre-hydrolyzed and the resulting pre-hydrolyzed solution is sprayed into the mineral admixture base powder. After aging, drying and sieving, grafted powder is obtained. (3) First, acidic silica sol with a particle size of 8-15 nm is introduced into the grafted powder, then alkaline silica sol with a particle size of 20-60 nm is introduced, and sodium methylsilicate aqueous solution is introduced when the material weight loss rate is 4%-6%. After drying and sieving, modified mineral admixture particles are obtained. (4) The modified mineral admixture particles, ordinary silicate cement and calcium oxide are mixed to obtain mineral admixture sludge solidification agent.

[0015] Preferably, in step (1), the metakaolin and the silica fume are dried at 105°C for 2 hours and then dry-mixed at 300 r / min for 15 minutes.

[0016] This invention achieves the following beneficial effects through a preparation path that uses metakaolin and silica fume composite mineral particles as a matrix, and sequentially performs pre-hydrolysis grafting, stepwise introduction of acidic small-particle-size and alkaline large-particle-size silica sol, introduction of sodium methylsilicate under a weight loss window, and finally composite with ordinary silicate cement and calcium oxide: First, the pre-hydrolysis and grafting treatment based on γ-aminopropyltriethoxysilane significantly improves the dispersibility and surface activity of the mineral admixture powder in subsequent liquid phase modification, providing a stable and uniform interface basis for the stepwise and orderly loading of subsequent functional components, and avoiding the ineffective consumption or encapsulation of organosilane during the later overall mixing.

[0017] Secondly, the stepwise and orderly introduction of acidic small-particle-size silica sol and alkaline large-particle-size silica sol constitutes a synergistic mechanism for pore refinement. The first introduced acidic small-particle-size sol can preferentially penetrate and act on the finest interparticle interface regions, promoting early and localized densification and nucleation of the gel products; the subsequently introduced alkaline large-particle-size sol, on this basis, plays a bridging and filling role, effectively blocking larger pores, thereby disrupting the continuity of water migration channels at multiple scales.

[0018] Furthermore, controlling the addition of sodium methylsilicate within a specific weight loss window is crucial for achieving a dense internal structure with an external hydrophobic gradient. This weight loss condition ensures that the internal densification network guided by silica sol has initially formed but is not completely dry. The sodium methylsilicate introduced at this point can migrate evenly to the outer layer of the particles and the pore throat openings with the help of residual moisture, forming a delayed-effect hydrophobic barrier. This barrier neither prematurely interferes with the densification process of the inner structure nor prevents the intrusion of external moisture later on.

[0019] Finally, ordinary silicate cement and calcium oxide are added after all surface modification steps to avoid interference from their early water absorption, heat release, and agglomeration on the surface modification reaction of mineral particles, ensuring that the above-mentioned multi-step interface engineering design can be carried out completely and independently. The modified mineral admixture particles are then mixed with cement, allowing the cement hydration products to fully fill and strengthen the pre-optimized microstructure framework. Ultimately, the solidified body simultaneously achieves high unconfined compressive strength, extremely low permeability coefficient and capillary water absorption height on a macroscopic scale, as well as excellent quality stability and strength retention after wet-dry cycles. Attached Figure Description

[0020] To more clearly illustrate the technical solutions in this invention or the prior art, the accompanying drawings used in the description of the embodiments or the prior art will be briefly introduced below.

[0021] Figure 1 This is a line graph showing the capillary water rise height of the solidified sludge prepared according to the present invention over time. Detailed Implementation

[0022] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to specific embodiments.

[0023] Raw materials and sources: Ordinary silicate cement is Holcim China Shuangma brand ordinary silicate cement P·O42.5 low alkali; metakaolin is Chao brand high-activity metakaolin KAOPOZZ; silica fume is Wuhan Newrich New Material Co., Ltd. silica fume NR92; acidic small-particle-size silica sol is Kuncheng Technology Co., Ltd. acidic silica sol, silica mass fraction 20%, particle size 8-15nm; alkaline large-particle-size silica sol is Kuncheng Technology Co., Ltd. large-particle-size silica sol, silica mass fraction 30%, particle size 20-60nm; sodium methylsilicate is Hangzhou Silitu New Material Technology Co., Ltd. Silway 713, solid content 30%, active ingredient 19%; silt is taken from urban river dredging wet mud, after natural drainage to remove shells, plant roots and impurities with a particle size greater than 2mm.

[0024] Example 1: Step 1: Weigh 250g of metakaolin and 100g of silica fume, and dry them separately at 105℃ for 2h to remove physically adsorbed water. After drying, cool them to room temperature in a desiccator, and then combine them and dry mix them in a stirring container at 300r / min for 15min to obtain 350g of mineral admixture base powder. Step 2: Weigh 90g of anhydrous ethanol, 10g of deionized water and 1g of glacial acetic acid, mix them evenly and then add 12g of γ-aminopropyltriethoxysilane. Stir at 25°C for 20min to obtain a pre-hydrolyzed solution. Then, atomize the pre-hydrolyzed solution into 350g of mineral admixture powder obtained in Step 1 within 10min, continue mixing at 300r / min for 30min, and then let it stand and age at 40°C for 1h. After aging, dry at 80°C for 2h, gently grind it in a mortar and pestle and pass it through a 200-mesh sieve to obtain grafted powder. Step 3: After cooling the grafted powder obtained in Step 2 to below 40℃, place it in a mixing container. First, atomize and spray 24g of acidic small-particle-size silica sol within 8 minutes, continue stirring for 20 minutes, and then seal and let stand for 20 minutes. Next, atomize and spray 18g of alkaline large-particle-size silica sol within 8 minutes, and continue stirring for 25 minutes. Then, spread the material evenly in an enamel pan, keep it at 55℃ and stir once every 10 minutes. When the weight loss is 5%, immediately premix 12g of sodium methylsilicate aqueous solution with 6g of deionized water and atomize and spray it within 5 minutes, continue stirring for 15 minutes, then let it stand at 60℃ for 1 hour and dry at 70℃ for 2 hours. Grind it in a mortar and pass it through a 200-mesh sieve to obtain modified mineral admixture particles. Step 4: Weigh 500g of ordinary Portland cement and 125g of calcium oxide, and put them together with 375g of modified mineral admixture particles obtained in Step 3 into a dry mixing container. Dry mix at 300r / min for 20min and then seal immediately to obtain a high impermeability and durability mineral admixture sludge curing agent. Step 5: When using, take 1000g of silt that has been granulated through a 2mm sieve and adjust its moisture content to 70%. The moisture content is calculated as the ratio of water mass to oven-dry soil mass. First, stir for 1 minute to break up the existing agglomerates. Then, add 220g of the curing agent obtained in Step 4 in three portions, with a 1-minute interval between each addition. After all the agent has been added, stir continuously for 5 minutes until the material has a uniform color and no visible dry powder lumps. Then, pour it into a mold and tamp it in two layers to form the shape. Let it stand for 24 hours before demolding. Then, seal and cure for 3 days, and continue to cure for 25 days at 25℃ and a relative humidity of not less than 95%.

[0025] Example 2: Step 1: Weigh 220g of metakaolin and 130g of silica fume, and dry them separately at 105℃ for 2h to remove physically adsorbed water. After drying, cool them to room temperature in a desiccator, and then combine them and dry mix them in a stirring container at 300r / min for 15min to obtain 350g of mineral admixture base powder. Step 2: Weigh 80g of anhydrous ethanol, 8g of deionized water and 0.8g of glacial acetic acid, mix them evenly and add 10g of γ-aminopropyltriethoxysilane. Stir at 25℃ for 20min to obtain a pre-hydrolyzed solution. Then, atomize the pre-hydrolyzed solution into 350g of mineral admixture powder obtained in Step 1 within 10min, continue mixing at 300r / min for 25min, and then let it stand and age at 40℃ for 1h. After aging, dry at 75℃ for 2h, gently grind it in a mortar and pestle and pass it through a 200-mesh sieve to obtain grafted powder. Step 3: After cooling the grafted powder obtained in Step 2 to below 40℃, place it in a mixing container. First, atomize and spray 20g of acidic small-particle-size silica sol within 8 minutes, continue stirring for 18 minutes, and then seal and let stand for 20 minutes. Next, atomize and spray 14g of alkaline large-particle-size silica sol within 8 minutes, and continue stirring for 20 minutes. Then, spread the material evenly in an enamel pan, keep it at 55℃ and stir once every 10 minutes. When the weight loss is 4%, immediately premix 10g of sodium methylsilicate aqueous solution with 4g of deionized water and atomize and spray it within 5 minutes, continue stirring for 15 minutes, then let it stand at 60℃ for 1 hour and dry at 70℃ for 2 hours. Grind it in a mortar and pass it through a 200-mesh sieve to obtain 365g of modified mineral admixture particles. Step 4: Weigh 450g of ordinary Portland cement and 100g of calcium oxide, and put them together with 365g of modified mineral admixture particles obtained in Step 3 into a dry mixing container. Dry mix at 300r / min for 20min and then seal immediately to obtain a high impermeability and durability mineral admixture sludge curing agent. Step 5: When using, take 1000g of silt that has been granulated through a 2mm sieve and adjust its moisture content to 70%. The moisture content is calculated as the ratio of water mass to oven-dry soil mass. First, stir for 1 minute to break up the existing agglomerates. Then, add 200g of the curing agent obtained in Step 4 in three portions, with a 1-minute interval between each addition. After all the agent has been added, stir continuously for 5 minutes until the material has a uniform color and no visible dry powder lumps. Then, pour it into a mold and tamp it in two layers to form the shape. Let it stand for 24 hours before demolding. Then, seal and cure for 3 days, and continue to cure for 25 days at 25℃ and a relative humidity of not less than 95%.

[0026] Example 3: Step 1: Weigh 270g of metakaolin and 80g of silica fume, and dry them separately at 105℃ for 2h to remove physically adsorbed water. After drying, cool them to room temperature in a desiccator, and then combine them and dry mix them in a stirring container at 300r / min for 15min to obtain 350g of mineral admixture base powder. Step 2: Weigh 100g anhydrous ethanol, 12g deionized water and 1.2g glacial acetic acid, mix them evenly and add 14g γ-aminopropyltriethoxysilane. Stir at 25℃ for 25min to obtain a pre-hydrolyzed solution. Then, atomize the pre-hydrolyzed solution into 350g of mineral admixture powder obtained in Step 1 within 10min, continue mixing at 300r / min for 35min, and then let it stand and age at 45℃ for 1h. After aging, dry at 80℃ for 2h, gently grind it in a mortar and pestle and pass it through a 200-mesh sieve to obtain grafted powder. Step 3: After cooling the grafted powder obtained in Step 2 to below 40℃, place it in a mixing container. First, atomize and spray 28g of acidic small-particle-size silica sol within 8 minutes, continue stirring for 22 minutes, and then seal and let stand for 20 minutes. Next, atomize and spray 22g of alkaline large-particle-size silica sol within 8 minutes, and continue stirring for 30 minutes. Then, spread the material evenly in an enamel pan, keep it at 58℃ and stir once every 10 minutes. When the weight loss is 6%, immediately premix 14g of sodium methylsilicate aqueous solution with 8g of deionized water and atomize and spray it within 5 minutes, continue stirring for 18 minutes, then let it stand at 60℃ for 1 hour and dry at 70℃ for 2 hours. Grind it in a mortar and pass it through a 200-mesh sieve to obtain 386g of modified mineral admixture particles. Step 4: Weigh 550g of ordinary Portland cement and 140g of calcium oxide, and put them together with 386g of modified mineral admixture particles obtained in Step 3 into a dry mixing container. Dry mix at 300r / min for 20min and then seal immediately to obtain a high impermeability and durability mineral admixture sludge curing agent. Step 5: When using, take 1000g of silt that has been granulated through a 2mm sieve and adjust its moisture content to 70%. The moisture content is calculated as the ratio of water mass to oven-dry soil mass. First, stir for 1 minute to break up the existing agglomerates. Then, add 240g of the curing agent obtained in Step 4 in three portions, with a 1-minute interval between each addition. After all the agent has been added, stir continuously for 5 minutes until the material has a uniform color and no visible dry powder lumps. Then, pour it into a mold and tamp it in two layers to form the shape. Let it stand for 24 hours before demolding. Then, seal and cure for 3 days, and continue to cure for 25 days at 25℃ and a relative humidity of not less than 95%.

[0027] Example 4: Step 1: Weigh 230g of metakaolin and 120g of silica fume, and dry them separately at 105℃ for 2h to remove physically adsorbed water. After drying, cool them to room temperature in a desiccator, and then combine them and dry mix them in a stirring container at 300r / min for 15min to obtain 350g of mineral admixture base powder. Step 2: Weigh 90g of anhydrous ethanol, 10g of deionized water and 1.0g of glacial acetic acid, mix them evenly and add 11g of γ-aminopropyltriethoxysilane. Stir at 25℃ for 20min to obtain a pre-hydrolyzed solution. Then, atomize the pre-hydrolyzed solution into 350g of mineral admixture powder obtained in Step 1 within 10min, continue mixing at 300r / min for 30min, and then let it stand and age at 40℃ for 1h. After aging, dry at 78℃ for 2h, gently grind it in a mortar and pestle and pass it through a 200-mesh sieve to obtain grafted powder. Step 3: After cooling the grafted powder obtained in Step 2 to below 40℃, place it in a mixing container. First, atomize and spray 26g of acidic small-particle-size silica sol within 8 minutes, continue stirring for 20 minutes, and then seal and let stand for 20 minutes. Next, atomize and spray 20g of alkaline large-particle-size silica sol within 8 minutes, and continue stirring for 25 minutes. Then, spread the material evenly in an enamel pan, keep it at 56℃ and stir once every 10 minutes. When the weight loss is 5%, immediately premix 13g of sodium methylsilicate aqueous solution with 6g of deionized water and atomize and spray it within 5 minutes, continue stirring for 15 minutes, then let it stand at 60℃ for 1 hour and dry at 70℃ for 2 hours. Grind it in a mortar and pass it through a 200-mesh sieve to obtain 376g of modified mineral admixture particles. Step 4: Weigh 480g of ordinary Portland cement and 110g of calcium oxide, and put them together with 376g of modified mineral admixture particles obtained in Step 3 into a dry mixing container. Dry mix at 300r / min for 20min and then seal immediately to obtain a high impermeability and durability mineral admixture sludge curing agent. Step 5: When using, take 1000g of silt that has been granulated through a 2mm sieve and adjust its moisture content to 70%. The moisture content is calculated as the ratio of water mass to oven-dry soil mass. First, stir for 1 minute to break up the existing agglomerates. Then, add 210g of the curing agent obtained in Step 4 in three portions, with a 1-minute interval between each addition. After all the agent has been added, stir continuously for 5 minutes until the material has a uniform color and no visible dry powder lumps. Then, pour it into a mold and tamp it in two layers to form the shape. Let it stand for 24 hours before demolding. Then, seal and cure for 3 days, and continue to cure for 25 days at 25℃ and a relative humidity of not less than 95%.

[0028] Example 5: Step 1: Weigh 260g of metakaolin and 90g of silica fume, and dry them separately at 105℃ for 2h to remove physically adsorbed water. After drying, cool them to room temperature in a desiccator, then combine them and dry mix them in a stirring container at 300r / min for 15min to obtain 350g of mineral admixture base powder. Step 2: Weigh 95g of anhydrous ethanol, 10g of deionized water and 1.0g of glacial acetic acid, mix them evenly and add 13g of γ-aminopropyltriethoxysilane. Stir at 25℃ for 20min to obtain a pre-hydrolyzed solution. Then, atomize the pre-hydrolyzed solution into 350g of mineral admixture powder obtained in Step 1 within 10min, continue mixing at 300r / min for 30min, and then let it stand and age at 40℃ for 1h. After aging, dry at 80℃ for 2h, gently grind it in a mortar and pestle and pass it through a 200-mesh sieve to obtain grafted powder. Step 3: After cooling the grafted powder obtained in Step 2 to below 40℃, place it in a mixing container. First, atomize and spray 22g of acidic small-particle-size silica sol within 8 minutes, continue stirring for 20 minutes, and then seal and let stand for 20 minutes. Next, atomize and spray 18g of alkaline large-particle-size silica sol within 8 minutes, and continue stirring for 25 minutes. Then, spread the material evenly in an enamel pan, keep it at 55℃ and stir once every 10 minutes. When the weight loss is 5%, immediately premix 12g of sodium methylsilicate aqueous solution with 5g of deionized water and atomize and spray it within 5 minutes, continue stirring for 15 minutes, then let it stand at 60℃ for 1 hour and dry at 70℃ for 2 hours. Grind it in a mortar and pass it through a 200-mesh sieve to obtain 379g of modified mineral admixture particles. Step 4: Weigh 520g of ordinary Portland cement and 130g of calcium oxide, and put them together with 379g of modified mineral admixture particles obtained in Step 3 into a dry mixing container. Dry mix at 300r / min for 20min and then seal immediately to obtain a high impermeability and durability mineral admixture sludge curing agent. Step 5: When using, take 1000g of silt that has been granulated through a 2mm sieve and adjust its moisture content to 70%. The moisture content is calculated as the ratio of water mass to oven-dry soil mass. First, stir for 1 minute to break up the existing agglomerates. Then, add 230g of the curing agent obtained in Step 4 in three portions, with a 1-minute interval between each addition. After all the agent has been added, stir continuously for 5 minutes until the material has a uniform color and no visible dry powder lumps. Then, pour it into a mold and tamp it in two layers to form the shape. Let it stand for 24 hours before demolding. Then, seal and cure for 3 days, and continue to cure for 25 days at 25℃ and a relative humidity of not less than 95%.

[0029] Comparative Example 1: The difference between Comparative Example 1 and Example 1 is as follows: In step 2, 90g of anhydrous ethanol, 10g of deionized water and 1g of glacial acetic acid were mixed evenly and then atomized and sprayed into 350g of mineral admixture base powder obtained in step 1 within 10min. The mixture was maintained at 300r / min and mixed for another 30min. Then it was allowed to stand at 40℃ for 1h. After aging, it was dried at 80℃ for 2h, gently ground in a mortar and passed through a 200-mesh sieve to obtain powder. In step 3, after cooling the powder obtained in step 2 to below 40℃, 24g of acidic small-particle-size silica sol was atomized and sprayed into it within 8min. The mixture was stirred for another 20min and then allowed to stand in a sealed container for another 20min. Then, 18g of alkaline large-particle-size silica sol was atomized and sprayed into it within 8min. The mixture was stirred for another 25min. The material was then spread evenly in an enamel pan, kept at 55°C and stirred every 10 minutes. When the weight loss was 5%, 12g of sodium methylsilicate aqueous solution and 6g of deionized water were premixed and sprayed into the pan through atomization within 5 minutes. The mixture was stirred for another 15 minutes, then allowed to stand at 60°C for 1 hour and dried at 70°C for 2 hours. The mixture was then ground in a mortar and passed through a 200-mesh sieve to obtain modified mineral admixture particles. In step 4, 500g of ordinary silicate cement and 125g of calcium oxide were weighed and added together with 375g of the modified mineral admixture particles obtained in step 3 into a dry mixing container. The mixture was dry-mixed at 300r / min for 20 minutes and then immediately sealed. In step 5, 12g of γ-aminopropyltriethoxysilane and 18g of deionized water were premixed and then added to the sludge in three separate batches, along with 220g of the curing agent obtained in step 4. The remaining conditions were the same as in Example 1.

[0030] Comparative Example 2: The difference between Comparative Example 2 and Example 1 is that in step 3, in order to ensure that the total amount of silica solid introduced is consistent with that in Example 1, instead of introducing 24g of acidic small-particle-size silica sol and 18g of alkaline large-particle-size silica sol in two separate steps, 51g of acidic small-particle-size silica sol is atomized and sprayed into the grafted powder obtained in step 2 in one go within 16min, and stirred for another 45min under sealed static conditions; then, after controlling the weight loss to 5% as in Example 1, a premix of 12g of sodium methylsilicate aqueous solution and 6g of deionized water is added, and the remaining conditions are the same as in Example 1.

[0031] Comparative Example 3: The difference between Comparative Example 3 and Example 1 is that in step 3, in order to ensure that the total amount of silica solid introduced is consistent with that in Example 1, instead of introducing 24g of acidic small-particle-size silica sol and 18g of alkaline large-particle-size silica sol in two separate steps, 34g of alkaline large-particle-size silica sol is atomized and sprayed into the grafted powder obtained in step 2 in one go within 12 minutes, and stirred for another 45 minutes under sealed static conditions; then, after controlling the weight loss to 5% as in Example 1, a premix of 12g of sodium methylsilicate aqueous solution and 6g of deionized water is added, and the remaining conditions are the same as in Example 1.

[0032] Comparative Example 4: The difference between Comparative Example 4 and Example 1 is as follows: In step 3, 24g of acidic small-particle-size silica sol and 18g of alkaline large-particle-size silica sol were premixed evenly and then atomized and sprayed into the grafted powder obtained in step 2 in one go within 8 minutes, and stirred for another 45 minutes under sealed static conditions; then, according to Example 1, the weight loss was controlled to be 5% and a premix of 12g of sodium methylsilicate aqueous solution and 6g of deionized water was added, and the remaining conditions were the same as in Example 1.

[0033] Comparative Example 5: The difference between Comparative Example 5 and Example 1 is that in step 3, when the weight loss is 10%, 12g of sodium methylsilicate aqueous solution is immediately premixed with 6g of deionized water and then atomized and sprayed into the solution within 5 minutes. The other conditions are the same as in Example 1.

[0034] Comparative Example 6: The difference between Comparative Example 6 and Example 1 is that in step 3, when the weight loss is 1%, 12g of sodium methylsilicate aqueous solution is immediately premixed with 6g of deionized water and then atomized and sprayed into the solution within 5 minutes. The other conditions are the same as in Example 1.

[0035] Comparative Example 7: The difference between Comparative Example 7 and Example 1 is as follows: Before step 2, 500g of ordinary silicate cement and 125g of calcium oxide were added together with 350g of mineral admixture powder obtained in step 1 into a mixing container and dry-mixed at 300r / min for 20min. Then, the process was continued according to steps 2 and 3 of Example 1. In step 4, no additional ordinary silicate cement and calcium oxide were added. The material obtained in step 3 was dry-mixed at 300r / min for 5min and then sealed immediately. The other conditions were the same as in Example 1.

[0036] Performance testing: Sample Preparation: The samples used for testing included the curing agents prepared in Examples 1-5 and Comparative Examples 1-7, and the solidified sludge samples prepared therefrom. Specifically, the curing agents obtained in step 4 of each example or comparative example were used to solidify 1000g of sludge that had been granulated through a 2mm sieve and adjusted to a moisture content of 70% according to the corresponding proportions. The sludge was stirred, molded, and cured according to step 5 of each example or comparative example. Unconfined compressive strength samples and wet-dry cycle samples were molded using a stainless steel cylindrical mold with an inner diameter of 39.1mm and a height of 80mm, with 6 parallel samples prepared for each group. Permeability coefficient samples and capillary water rise height samples were molded using a ring cutter mold with an inner diameter of 61.8mm and a height of 40mm, with 6 parallel samples prepared for each group. All solidified sludge samples were cured at 25℃ and a relative humidity of not less than 95% for 28 days before testing. The particle samples used for intrinsic characterization were the modified mineral admixture particles obtained in step 3, which were placed in a desiccator for equilibration for 24 hours before testing. Unless otherwise stated, all test results are the average of parallel samples, and the results are shown in Table 1.

[0037] 28-day unconfined compressive strength: The unconfined compressive strength test was conducted on the 28-day solidified silt cylindrical specimens of Examples 1-5 and Comparative Examples 1-7 according to GB / T 50123-2019 "Standard for Geotechnical Testing Methods". Before testing, the specimen surface was wiped until there was no standing water, and the initial height and diameter of the specimen were measured to an accuracy of 0.02 mm. Strain-controlled loading was used, with the axial loading rate fixed at 1.00 mm / min, and loading was stopped when the peak load was reached or the axial strain reached 15%. Six parallel samples were tested for each group of specimens. After removing the highest and lowest values, the average of the remaining four results was taken as the 28-day unconfined compressive strength.

[0038] Permeability coefficient: The 28-day solidified silt ring specimens from Examples 1-5 and Comparative Examples 1-7 were tested according to the variable head permeability test (T0130-2007) in JTG 3430-2020 "Specifications for Geotechnical Testing of Highways". The specimen dimensions were 61.8 mm inner diameter and 40 mm height. Before testing, the specimens were vacuumed at -0.08 MPa for 30 minutes and then immersed in degassed pure water for 24 hours to achieve saturation. The saturated specimens were placed in a variable head permeability device. The test water temperature was controlled at 23±1℃, the initial head difference was set to 150 cm, and the head difference throughout the process was not greater than 2 m. The time taken for the variable head to decrease from 150 cm to 50 cm was recorded. This was repeated 5-6 times. When the relative deviation of the permeability coefficient calculated from three consecutive measurements was not greater than 10%, the average value was taken and converted to the permeability coefficient under 20℃ conditions. The results are shown in Table 1.

[0039] Capillary water rise height: The capillary water rise height test was performed on the 28-day solidified silt ring specimens of Examples 1-5 and Comparative Examples 1-7 according to T0128-1993 of JTG 3430-2020 "Specifications for Geotechnical Testing of Highways". Before testing, the sidewalls of the specimens were sealed with polyethylene film and paraffin wax, leaving only the bottom and top surfaces open to ensure unidirectional axial migration of water. The specimens were then dried in a 40℃ forced-air oven until constant mass, cooled to room temperature, and sealed for 24 hours. During the test, the bottom surface of the specimen was in contact with deionized water, with an immersion depth controlled at 5 mm and an ambient temperature controlled at 20±2℃. The water front rise height was recorded at 0.5h, 1h, 2h, 4h, 8h, 24h, 48h, and 72h. After 72h, the specimen was split along its axial direction, and the average height of the wetting front was measured as the capillary water rise height result. The results are shown in Table 1 and Table 2. Figure 1 As shown.

[0040] Mass loss rate and strength retention rate after wet-dry cycling: The wet-dry cycling treatment was carried out according to the humidity adjustment and cycling conditions in T0192-2019 of JTG 3430-2020 "Specifications for Geotechnical Testing of Highways". The strength determination after cycling was carried out according to the unconfined compressive strength test in GB / T 50123-2019 "Standard for Geotechnical Testing Methods". The test samples were 28-day solidified silt cylindrical specimens from Examples 1-5 and Comparative Examples 1-7. Six parallel samples were taken from each group, of which three were used to determine the 28-day baseline unconfined compressive strength, and the other three were used for wet-dry cycling. The surface-dried mass after 28 days of curing was denoted as m0. In each cycle, water was slowly added to the sample through the top permeable stone until the sample mass reached m0 + 4%. The sample was then placed in a sealed humidifier for 48 hours. Next, the sample was dried in a 40℃ forced-air oven until the mass decreased to m0 - 4%. After removal, it was placed in a sealed humidifier for 24 hours, completing one cycle. A total of five cycles were performed. The mass loss rate was calculated after five cycles. Subsequently, the sample was placed at room temperature for 24 hours, and the unconfined compressive strength after the cycles was measured. The strength retention rate was calculated as (unconfined compressive strength after the cycles / 28-day baseline unconfined compressive strength) × 100%. The results are shown in Table 1.

[0041] Table 1 Performance Test Results

[0042] Data Analysis: From Table 1 and Figure 1The data from the embodiments show that the high impermeability and durability mineral-blended sludge solidifying agent prepared by the present invention exhibits a good balance between strength formation, water migration resistance, and wet-dry stability. This may be because metakaolin and silica fume are first used as composite mineral particles for water-limited pre-hydrolysis grafting, which can improve particle dispersion and interface wetting; acidic small-particle-size silica sol preferentially acts on fine interfaces and promotes local nucleation, while alkaline large-particle-size silica sol subsequently plays an outer layer bridging and densification role; the addition of sodium methylsilicate under appropriate weight loss avoids prematurely blocking the normal gelation process, allowing the gelation products to accumulate in the pore throat region and gradually form a delayed hydrophobic barrier on the outer layer, thus taking into account strength, impermeability, and durability.

[0043] From Table 1 and Figure 1 The data from Example 1 and Comparative Example 1 show that when other conditions are basically the same, but γ-aminopropyltriethoxysilane is added to the sludge simultaneously with the curing agent, the impermeability, capillary water-blocking ability, and wet-dry stability of the cured body all decrease significantly. The main reason is that the added γ-aminopropyltriethoxysilane is in a complex system with high water content and containing ordinary silicate cement and calcium oxide, and it is difficult to preferentially fix on the surface of metakaolin and silica fume particles. This makes it difficult for the subsequent acidic small-particle-size silica sol, alkaline large-particle-size silica sol, and sodium methylsilicate to establish a stable and continuous interface layer.

[0044] From Table 1 and Figure 1 The data from Example 1 and Comparative Example 2 show that when only acidic small-particle-size silica sol is introduced at once without the stepwise layering of alkaline large-particle-size silica sol, although the system can maintain a certain strength, the permeability coefficient, capillary water absorption inhibition, and post-cycle structure retention are all inferior to those of the examples. This is presumably because acidic small-particle-size silica sol is better at penetrating fine interfaces and providing nucleation sites, which is beneficial for local filling and early densification. However, it lacks the bridging, overlapping, and outer-layer sealing effects of subsequent larger-particle-size particles, and local continuous water migration paths are still easily preserved between pore throats.

[0045] From Table 1 and Figure 1 The data from Example 1 and Comparative Examples 3 and 4 show that, regardless of whether only alkaline large-particle-size silica sol is used, or whether acidic small-particle-size silica sol is premixed with alkaline large-particle-size silica sol and then added all at once, the resulting cured body is inferior to the stepwise introduction scheme in terms of impermeability and durability. The degradation is more pronounced when using only alkaline large-particle-size silica sol. The reason for this may be that larger-particle-size particles are more suitable for outer layer bridging and pore sealing, but without the nucleation of small-particle-size particles and interface wetting, the internal fine pores are difficult to be fully occupied; and adding it all at once after premixing weakens the original sequence of densification of the inner layer followed by stabilization of the outer layer.

[0046] From Table 1 and Figure 1Data from Example 1 and Comparative Example 5 show that when sodium methylsilicate is added prematurely while the weight loss is still at a high level, the strength, impermeability, and wet-dry cycle stability of the cured body all decrease significantly. The reason for this is presumably that under excessive weight loss, sodium methylsilicate is more likely to preferentially distribute with moisture on the outer layer of the particles, prematurely forming localized hydrophobic regions. This, in turn, shields the subsequent formation of a dense network from acidic small-particle-size silica sol and alkaline large-particle-size silica sol, making it difficult for the cementitious products formed by ordinary silicate cement and calcium oxide to continuously fill the pores and throats.

[0047] From Table 1 and Figure 1 Data from Example 1 and Comparative Example 6 show that when sodium methylsilicate is added after the weight loss has been reduced too much, the permeability, capillary water absorption, and post-cycle retention further deteriorate. The main reason for this is likely that the particle surface and local pores are already excessively dry at this point, making it difficult for sodium methylsilicate to migrate evenly and distribute deeply with the help of sufficient moisture. Instead, it remains mostly on the outer surface, resulting in a surface layer with some hydrophobic effect but insufficient continuous hydrophobic network inside. This structure is prone to inconsistent internal and external responses during subsequent moisture absorption and loss, thus amplifying the propagation of microcracks under wet-dry cycles.

[0048] From Table 1 and Figure 1 Data from Example 1 and Comparative Example 7 show that adding ordinary silicate cement and calcium oxide before surface modification leads to an overall decrease in strength, impermeability, and durability. This is presumably because the early addition of ordinary silicate cement and calcium oxide causes them to absorb water and release heat, promoting powder agglomeration. This prematurely occupies or blocks accessible sites on the metakaolin and silica fume surfaces, weakening the effective grafting of γ-aminopropyltriethoxysilane and the directional deposition of the two types of silica sols. Even with subsequent addition of sodium methylsilicate, localized adhesion is more likely, making it difficult to form a continuous and stable multilayered interface structure.

[0049] Those skilled in the art should understand that the discussion of any of the above embodiments is merely exemplary and is not intended to imply that the scope of the invention is limited to these examples; within the framework of the invention, the technical features of the above embodiments or different embodiments can also be combined, and there are many other variations of the different aspects of the invention as described above, which are not provided in detail for the sake of brevity.

Claims

1. A mineral-blended sludge solidifying agent, characterized in that, By weight, it includes: 365-386 parts modified mineral admixture particles, 450-550 parts ordinary Portland cement, and 100-140 parts calcium oxide; The modified mineral blend particles are obtained by grafting metakaolin and silica fume with γ-aminopropyltriethoxysilane, followed by sequential introduction of acidic silica sol with a particle size of 8-15 nm and alkaline silica sol with a particle size of 20-60 nm, and then introducing sodium methylsilicate aqueous solution when the weight loss rate is 4%-6%. The raw materials used to prepare the modified mineral blend particles, by weight, include 220-270 parts metakaolin, 80-130 parts silica fume, 10-14 parts γ-aminopropyltriethoxysilane, 20-28 parts acidic silica sol with a particle size of 8-15 nm, 14-22 parts alkaline silica sol with a particle size of 20-60 nm, and 10-14 parts sodium methylsilicate aqueous solution; The acidic silica sol has a silica mass fraction of 20%. The alkaline silica sol has a silica mass fraction of 30%. The weight loss rate is the percentage of the mass reduction before and after drying at 105°C for 30 minutes relative to the mass before drying.

2. The mineral-blended sludge solidifying agent according to claim 1, characterized in that, The sodium methylsilicate aqueous solution was premixed with deionized water before being introduced.

3. The mineral-blended sludge solidifying agent according to claim 1, characterized in that, The modified mineral blend particles are obtained by grinding and passing them through a 200-mesh sieve.

4. A method for preparing a mineral-blended sludge solidifying agent according to any one of claims 1-3, characterized in that, Includes the following steps: (1) After drying, metakaolin and silica fume are mixed to obtain mineral admixture base powder; (2) γ-aminopropyltriethoxysilane is pre-hydrolyzed and the resulting pre-hydrolyzed solution is sprayed into the mineral admixture base powder. After aging, drying and sieving, grafted powder is obtained. (3) First, acidic silica sol with a particle size of 8-15 nm is introduced into the grafted powder, then alkaline silica sol with a particle size of 20-60 nm is introduced, and sodium methylsilicate aqueous solution is introduced when the material weight loss rate is 4%-6%. After drying and sieving, modified mineral admixture particles are obtained. (4) The modified mineral admixture particles, ordinary silicate cement and calcium oxide are mixed to obtain a mineral admixture sludge solidifying agent; In step (2), the pre-hydrolyzed solution is composed of 80-100 parts anhydrous ethanol, 8-12 parts deionized water, 0.8-1.2 parts glacial acetic acid and 10-14 parts γ-aminopropyltriethoxysilane by mass.

5. The method for preparing the mineral-blended sludge solidifying agent according to claim 4, characterized in that, In step (1), the metakaolin and the silica fume are dried at 105°C for 2 hours and then dry-mixed at 300 r / min for 15 minutes.

Citation Information

Patent Citations

  • Luminous pervious concrete and preparation method thereof

    CN119661148A

  • High-strength sludge solidified soil and preparation method thereof

    CN119954486A